Interdisciplinary and interprofessional communication intervention: How psychological safety fosters communication and increases patient safety - Dietl, Johanna Elisa; Derksen, Christina; Keller, Franziska Maria; Lippke, Sonia (Frontiers in Psychology, 2023)
Background: Effective teamwork and communication are imperative for patient safety and quality care. Communication errors and human failures are considered the main source of patient harm. Thus, team trainings focusing on communication and creating psychologically safe environments are required. This can facilitate challenging communication and teamwork scenarios, prevent patient safety risks, and increase team performance perception. The sparse research concerning communication interventions calls for an understanding of psychological mechanisms. Therefore, this study investigated mechanisms of an interpersonal team intervention targeting communication and the relation of psychological safety to patient safety and team performance perception based on the applied input-process-output model of team effectiveness. Methods: Before and after a 4-hour communication intervention for multidisciplinary teams, a paper-pencil survey with N = 137 healthcare workers from obstetric units of two university hospitals was conducted. Changes after the intervention in perceived communication, patient safety risks and team performance perception were analyzed via t-tests. To examine psychological mechanisms regarding psychological safety and communication behavior, mediation analyses were conducted. Results: On average, perceived patient safety risks were lower after the intervention than prior to the intervention (MT1 = 3.220, SDT1 = 0.735; MT2 = 2.887, SDT2 = 0.902). This change was statistically significant t(67) = 2.760, p = .007. However, no such effect was found for interpersonal communication and team performance perception. Results illustrate the mediating role of interpersonal communication between psychological safety and safety performances operationalized as perceived patient safety risks (α1*β1 = -.163, 95% CI [-0.310, -0.046]) and team performance perception (α1*β1 = .189, 95% CI [0.044, 0.370]). Discussion: This study demonstrates psychological mechanisms of a communication team training to foster safety performances and psychological safety as an important predecessor for interpersonal communication. Our results highlight the importance of teamwork for patient safety. The interpersonal and interprofessional team training represents a novel approach as it empirically brings together interpersonal communication and collaboration in the context of patient safety. Future research should work on follow-up measures in randomized-controlled trials to broaden an understanding of changes over time.